How to Attract Your Students to Your Games: The Difference of Mediating Effect of Psychic Income on the Relationship between Points of Attachment and Behavioral Attributes - Jinwook Chung; Yong-Chae Rhee; Wonyoung Kim (Journal of Applied Sports Management, 2020)
The purpose of the current study was to examine the impact of the points of attachment with the mediating impact of college students’ psychic income on their attendance and word-of-mouth behavioral intentions. A total of 537 samples were collected from college students at a mid-sized southwest university in the United States. A CFA was conducted to evaluate the psychometric properties of the scales. The hypothesized model was tested using a SEM with AMOS 26 software. Additionally, a bootstrapping method was employed to determine the indirect effect of the mediating variable of psychic income on the relationship between points of attachment and behavioral intentions as well as points of attachment and word of mouth. The results reveal that psychic income mediated the proposed relationships.
Keywords: Athletic Administration; Collegiate Sport; Consumer Behavior; Marketing; WOM